The intensities of various forms of physical activity in physical education programs offered by universities for female students - Robert Podstawski; Marta A. Żurawik; Cain C. T. Clark; Ferenc Ihasz; Piotr Żurek (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: This study aimed to evaluate the effectiveness of various forms of physical activity (PA) among female students in physical education (PE) programs offered by universities in Poland, Hungary, and the United Kingdom. Methods: Two hundred full-time female university students (mean age: 19.93±0.82) enrolled in various PA programs. The participants' anthropometric traits were measured, and their body composition parameters were determined with the InBody analyzer. Based on the students' physiological parameters, the effectiveness of various types of PA was measured with Suunto Ambit3 peak heart rate monitors during 60 minutes of physical exertion. Results: The average values of body mass index (BMI), body fat mass (BFM), percent body fat (PBF), waist-hip ratio (WHR), visceral fat level (VFL), and obesity degree were significantly (p<0.05) lower among students who participated in jogging followed by sauna (JFBS), performed martial arts and attended general physical education (PE) classes. Physiological parameters were the highest in the martial art group, followed by JFBS and swimming groups, and they were significantly (p<0.05) higher than the values recorded in other PA groups (golf, aerobics, general PE classes, cycling, and individual training). Physiological parameters were significantly (p<0.05) lower among students who played golf and trained individually. Conclusions: Martial arts, JFBS, and swimming were the most effective types of PA among female university students. Students performing martial arts and JFBS had relatively lower body fat levels, whereas students who practiced swimming had the highest body fat levels in the population sample.